2017
DOI: 10.1016/j.jacc.2017.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding-Related Deaths in Relation to the Duration of Dual-Antiplatelet Therapy After Coronary Stenting

Abstract: Bleeding was strongly associated with the occurrence of mortality within 1 year after the bleeding event. Shorter compared with longer DAPT was associated with lower risk for bleeding-related death, a finding that may underlie the lower all-cause mortality with shorter DAPT in the RCTs of different DAPT durations after DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 29 publications
2
77
2
Order By: Relevance
“…Similarly, 2 year follow up of the ITALIC trial of 1850 patients randomized to 6 versus 24 month of DAPT after DES PCI found no difference in ischemic or bleeding endpoints, although there was a trend to higher mortality with longer DAPT (2.2% vs 1.2%; P = 0.11) . The same trend was seen by Palmerini et al through a meta‐analysis of six RCTs linking shorter DAPT with a lower all‐cause mortality, and lower rates of bleeding related death (HR: 0.65; 95%CI: 0.43‐0.99; P = 0.04). Given the mechanistic plausibility of the authors' finding, bleeding risk should be individually assessed prior to prolonging DAPT.…”
Section: Dual Antithrombotic Therapy After Pcisupporting
confidence: 76%
“…Similarly, 2 year follow up of the ITALIC trial of 1850 patients randomized to 6 versus 24 month of DAPT after DES PCI found no difference in ischemic or bleeding endpoints, although there was a trend to higher mortality with longer DAPT (2.2% vs 1.2%; P = 0.11) . The same trend was seen by Palmerini et al through a meta‐analysis of six RCTs linking shorter DAPT with a lower all‐cause mortality, and lower rates of bleeding related death (HR: 0.65; 95%CI: 0.43‐0.99; P = 0.04). Given the mechanistic plausibility of the authors' finding, bleeding risk should be individually assessed prior to prolonging DAPT.…”
Section: Dual Antithrombotic Therapy After Pcisupporting
confidence: 76%
“…First, bleeding complications are associated with adverse outcomes after PCI [12], risk stratification is important for such patients to enable an appropriate therapeutic approach for each individual case. In contemporary primary PCI, the occurrence of access site bleeds is rare even in high risk population [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy (DAPT) with aspirin and a P2Y 12 inhibitor reduces ischaemic recurrences in patients with ACS treated with percutaneous coronary intervention (PCI), but increases bleeding [7]. In this regard, approximately half of the major bleeds in patients aged 75 years or older are gastrointestinal bleeding (GIB) [8], an uncommon but devastating complication of regular antiplatelet use is intracerebral haemorrhage (ICH) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Of note, this inferiority may induce bleeding-related death. To explore whether single antiplatelet therapy could reduce the risk of bleeding, an open-label, multicentre, randomised, controlled trial was induced.…”
Section: Rational For Single Antiplatelet Therapymentioning
confidence: 99%